Recurso didático como facilitador no ensino de genética: uma perspectiva no campo da inclusão educacional - Antonio, Bárbara Cunha Padilha (Universidade Federal de São Carlos, 2021)
The New Biology has had a lot of visibility in the media. This theme integrates current technologies related to DNA and their new applications in the field of genetics. Any questioning about the scientific advance in technologies related to this area has guided ethical and social issues to the scientific world. Several studies related to teaching in the area of genetics converge in saying that this is considered difficult for students to learn, including students with vision difficulties. Thus, it is important to apply methodologies and use tools that support their understanding. In this context, didactic resources are great options as aids for content consolidation and to allow students to interact in the classroom, also helping in educational inclusion. The present work had as its general objective to verify the understanding of the difficulties and possibilities by Science and Biology teachers, from public and private schools, about an inclusive teaching resource elaborated from low-cost materials, designed for people with visual impairment - blind or with low vision - built to assist in learning a genetics content in basic education classrooms. The resource was made to work on concepts from Mendel's first law, with emphasis on the genotype/phenotype and dominance/recessiveness relationship. The phenotype selected was sensitivity to Phenylthiocarbamide (PTC). Styrofoam spheres and biscuit dough were used for its construction to represent the cell and its receptor, and biscuit with adhered beads to represent the genotypes (chromosomes/alleles). Data were obtained through an online questionnaire in order to obtain the teachers' evaluations (n=10) about the resource, and for its analysis the methodological instrument of Content Analysis by Laurence Bardin (2002) was used. As primary results of the research, it was found that the constructed didactic resource can be an important element that facilitates the understanding of concepts considered complex, of abstractions, promoting a more significant learning, which may help in inclusion and requiring initial and continued training in addition to planning teachers to use and build effective resources.
Didactic resource as a facilitator in genetics teaching: a perspective in the field of inclusive education
Keywords: Herança Mendeliana; mendelian inheritance; Deficiência visual; Visual impairment; Cegos; Blind; Baixa visão; Low vision; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO